A REVIEW ON CONSUMER BEHAVIOR IN REAL ESTATE PURCHASING: FACTORS INFLUENCING PURCHASE DECISIONS - Abdullah Bedi; Cokki Cokki (Graduate Program of Universitas Tarumanagara, 2026)
This article presents a structured narrative review of consumer behavior in property purchasing in Indonesia by analyzing 36 scholarly articles selected through a rigorous, multi-stage screening process. Using clear inclusion and exclusion criteria, the review integrates four main theoretical frameworks—namely the Theory of Planned Behavior, Prospect Theory, Maslow’s Hierarchy of Needs, and the Consumer Decision-Making Model—to explain the psychological, social, and economic dynamics influencing property purchase decisions in Indonesia. The findings indicate that attitudes, perceived behavioral control, risk aversion, income stability, and shifting lifestyle aspirations are dominant factors, accompanied by contextual influences such as the use of digital channels, sustainability preferences, and changing housing needs in the post-pandemic era. Prospect Theory helps explain the strong tendency toward loss aversion among Indonesian property buyers, while Maslow’s theory highlights the shift in needs from mere shelter to comfort, security, and social status. This review identifies a critical gap in the dominance of single-theory approaches in previous studies, emphasizing the need for a more comprehensive multi-theoretical model to better understand the complexity of Indonesia’s property market behavior. The article offers insights for policymakers, developers, and practitioners in formulating strategies that are more responsive to evolving consumer behavior in Indonesia’s dynamic property sector.